The Evolution of Modern Ablative Surgery for the Treatment of Obsessive-Compulsive and Major Depression Disorders - Mustroph, Martina Laetitia; Cosgrove, G. Rees; Williams, Ziv M. (Frontiers in Integrative Neuroscience, 2022)
In this review, we describe the evolution of modern ablative surgery for intractable psychiatric disease, from the original image-guided cingulotomy procedure described by Ballantine, to the current bilateral anterior cingulotomy using MRI-guided stereotactic techniques. Extension of the single lesion bilateral cingulotomy to the extended bilateral cingulotomy and subsequent staged limbic leucotomy (LL) is also discussed. Other ablative surgeries for psychiatric disease including subcaudate tractotomy (SCT) and anterior capsulotomy (AC) using modern MRI-guided ablative techniques, as well as radiosurgical capsulotomy, are described. Finally, the potential emerging role of MR-guided focused ultrasound (MRgFUS) for treating conditions such as major depressive disorder (MDD) and obsessive-compulsive disorder (OCD) is discussed.